Izbira optimalnih odločitev pri upravljanju s proizvodnim sistemom ob upoštevanju javnega mnenja - Zadnik Stirn, Lidija (Uporabna informatika (Ljubljana), 1999)
The article presents a model and methodology of searching for optimal decisionin a production system management which should be economically justified, environmentally harmless and acceptable to the public at the same time. We start from the fact that the possible production system management decisions supported by appropriate economic,ecological and technological considerations are known to us. These decisions are then presented to the public in the form of decision concepts. The public responds by determing the order of such decisions based on their preferences and benefits which they see as a result of the decisions proposed. The assessments on the part of the public are evaluated by means of conjoint analisys. The values obtained are then used together with economic and ecological values of decisions in a multi-criteria decision model which yields an optimal production system management solution with regard to economic, ecological, technological and social criteria.
Keywords: javno mnenje; kriteriji; odločanje; proizvodni sistemi; upravljanje